Effects of vehicular whole-body vibration on focus measured by a mobile app for brain training: A pilot study on the influence of gender and Attention Deficit Hyperactivity Disorder. - Duarte, Maria Lúcia Machado; Costal, Glauber Zerbini; Martinelli, Sthéfani Ferreira; Neves, Jorge Alexandre Barbosa (Work, 2020)
BACKGROUND: Students, as well as other professional drivers, must have focus to adequately perform their tasks. However, they are subjected to whole-body vibration (WBV) in their journey to school or work. OBJECTIVE: To investigate the influence of in-loco WBV exposure on focus, both instantaneously, as well as residually. Analysis is performed for both genders, as well as for the presence of Attention Deficit Hyperactivity Disorder (ADHD). METHODS: Using a tablet computer, 20 volunteers played a focus game available on an app for brain training while exposed or not exposed to WBV. The exposure was that of a car travelling on a stone paved route. The performance measure was the score provided at the end of each game. Subjective comfort and difficulty evaluations were also investigated. RESULTS: The results suggest that WBV had a negative effect on the focus performance. However, it proved positive three minutes after the exposure (residual effect). The mean scores of females were higher than for males for most of the tests, apart from the one under WBV although at the expense of getting more discomfort. The difficulty level was not different within the gender groups. CONCLUSION: It could be concluded that the group with ADHD had a small but positive influence on the results for most of the tests, indicating that they are less affected by the presence of WBV. Since many students and workers have ADHD, this may be considered an important finding. It was shown that objective results should not be the only measures to use, as the subjective evaluation may explain the results better.